Alcohol and hepatocellular carcinoma. Issue 1 (3rd April 2019) - Matsushita, Hiroshi; Takaki, Akinobu
Abstract : Background: Alcohol is classified as a Group 1 carcinogen by the International Agency for Research on Cancer because it induces hepatocellular carcinoma (among other cancers) in humans. An excessive alcohol intake may result in fatty liver, acute/chronic hepatitis, and cirrhosis and eventually lead to hepatocellular carcinoma. It has been reported that alcohol abuse increases the relative risk of hepatocellular carcinoma by 3- to 10-fold. Aim and Methods: To clarify the known mechanisms of alcohol-related carcinogenesis, we searched Pubmed using the terms alcohol and immune mechanism, alcohol and cancer, and immune mechanism and cancer and summarized the articles as a qualitative review. Results: From a clinical perspective, it is well known that alcohol interacts with other factors, such as smoking, viral hepatitis, and diabetes, leading to an increased risk of hepatocellular carcinoma. There are several possible mechanisms through which alcohol may induce liver carcinogenicity, including the mutagenic effects of acetaldehyde and the production of ROS due to the excessive hepatic deposition of iron. Furthermore, it has been reported that alcohol accelerates hepatitis C virus-induced liver tumorigenesis through TLR4 signaling. Despite intense investigations to elucidate the mechanisms, they remain poorly understood. Conclusion: This review summarizes the recent findings of clinical and pathological studies that have investigated the carcinogenic effects of alcohol in the liver.